2013
DOI: 10.1128/aac.01288-13
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Eravacycline (TP-434), a Novel Fluorocycline, against Hospital and Community Pathogens

Abstract: Eravacycline (TP-434 or 7-fluoro-9-pyrrolidinoacetamido-6-demethyl-6-deoxytetracycline) is a novel fluorocycline that was evaluated for antimicrobial activity against panels of recently isolated aerobic and anaerobic Gram-negative and Gram-positive bacteria. Eravacycline showed potent broad-spectrum activity against 90% of the isolates (MIC 90 ) in each panel at concentrations ranging from <0.008 to 2 g/ml for all species panels except those of Pseudomonas aeruginosa and Burkholderia cenocepacia (MIC 90 values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
190
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(206 citation statements)
references
References 36 publications
7
190
0
2
Order By: Relevance
“…The rise in resistance to early-generation tetracyclines has spurred the development of next-generation derivatives, including tigecycline (approved for human use in 2005) 15 , and eravacycline and omadacycline (currently in late-stage clinical trials) 16,17 . These newer drugs are designed to evade resistance by efflux or ribosomal protection, but they are largely untested against tetracycline-inactivating enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rise in resistance to early-generation tetracyclines has spurred the development of next-generation derivatives, including tigecycline (approved for human use in 2005) 15 , and eravacycline and omadacycline (currently in late-stage clinical trials) 16,17 . These newer drugs are designed to evade resistance by efflux or ribosomal protection, but they are largely untested against tetracycline-inactivating enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tetracyclines ranked in the top three antibiotics in both clinical prescriptions in the United States in 2010 (representing 15% of all antibiotic prescriptions) and in global sales for animal use in 2009 ($500 million in sales) 14 . Furthermore, next-generation derivatives are currently fueling a tetracycline renaissance, with the 2005 clinical approval of tigecycline 15 and ongoing late-stage clinical trials of eravacycline and omadacycline 16,17 justifying urgent interrogation of emerging and novel tetracycline resistance mechanisms. Previously, tetracycline resistance was thought to occur almost exclusively by two mechanisms: ribosomal protection or antibiotic efflux 13,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the broad-spectrum agent eravacycline (a new fluorocycline) also lacks activity against A. baumannii, B. cenocepacia, and P. aeruginosa (949,952). Plazomicin is a new aminoglycoside derivative of sisomicin with significant activity against a range of Gram-positive and Gram-negative bacteria (including multidrug-resistant isolates) (953,954).…”
Section: Multidrug Efflux Pumps As a Challenge In Drug Developmentmentioning
confidence: 99%
“…Eravacycline was designed to be active against the two main acquired tetracycline-specific resistance mechanisms, ribosomal protection and active drug efflux (9,10). In in vitro studies, the compound has shown potent activity against a broad spectrum of susceptible and multidrug-resistant bacteria, including Gram-negative, Gram-positive, and anaerobic bacteria (11). Eravacycline has a potency profile similar to that of carbapenems except that it more broadly covers Gram-positive pathogens, like methicillin-resistant Staphylococcus aureus and enterococci, is active against carbapenem-resistant Gram-negative bacteria, but is not active against Pseudomonas aeruginosa (8).…”
mentioning
confidence: 99%